Principal-agent problems in the purchase of durables: Evidence from motorcycles in Nepal - Massimo Filippini; Nirmal Kumar Raut; Suchita Srinivasan; Keshav Sureka (ETH Zurich, CER-ETH - Center of Economic Research, 2024)
We investigate the existence of a principal-agent problem between parents and financially dependent adult children within households on the purchase of a durable (such as a vehicle). We theoretically argue that children will select more expensive durables if parents contribute more towards its purchase, however this effect is weaker for altruistic children. We test this empirically using unique data collected on motorcycle purchases of university students in Kathmandu Valley, Nepal. We confirm the first hypothesis, however we show that altruism does not influence this relationship. Policy implications relate to the effects on household finances, and on possible environmental impacts.
Keywords: D1; D8; Q4; Q5; 330; Principal-agent problems; Intra-household decision-making; Durable adoption; Motorcycle; Nepal